Surveillance on Artificial Colours in Different Ready to Eat Foods - Ashfaq, Nadia; Masud, Tariq (Pakistan Journal of Nutrition, 2002)
Different types of ready to eat foods were analyzed for the detection and estimation of the added synthetic food colours. A total of 72 different samples of sweet meats and confectioneries were randomly collected from large and small shops of Rawalpindi Cantt. Quantities of the permitted colouring matter among the tested samples were found within the range of 18-220 ppm. 47.56% of the samples contained non-permitted food colours. Incidences of the use of non-permitted food colours and colours above permissible limits were higher in case of the unorganized food makers.